2013
DOI: 10.1016/j.ccr.2013.02.016
|View full text |Cite|
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase Siah2 Contributes to Castration-Resistant Prostate Cancer by Regulation of Androgen Receptor Transcriptional Activity

Abstract: SUMMARY Understanding the mechanism underlying the regulation of the androgen receptor (AR), a central player in the development of castration-resistant prostate cancer (CRPC), holds promise for overcoming the challenge of treating CRPC. We demonstrate that the ubiquitin ligase Siah2 targets a select pool of NCOR1-bound, transcriptionally-inactive AR for ubiquitin-dependent degradation, thereby promoting expression of select AR target genes implicated in lipid metabolism, cell motility, and proliferation. Siah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 29 publications
9
157
0
Order By: Relevance
“…Of note, nuclear SIAH2 was detected in 144 tumors and was linked to a shorter time to BF, which was seen in 22 patients in a 2.3 year follow-up analysis [87]. Furthermore, SIAH2 regulates the PSA gene under low and physiologic concentrations of androgens [41] and this could be linked to prostate cancer recurrence. These data rather suggest tumorpromoting functions of SIAH2 in this type of cancer.…”
Section: Expression Of Siahs In Primary Human Prostate Cancers and Pomentioning
confidence: 91%
See 2 more Smart Citations
“…Of note, nuclear SIAH2 was detected in 144 tumors and was linked to a shorter time to BF, which was seen in 22 patients in a 2.3 year follow-up analysis [87]. Furthermore, SIAH2 regulates the PSA gene under low and physiologic concentrations of androgens [41] and this could be linked to prostate cancer recurrence. These data rather suggest tumorpromoting functions of SIAH2 in this type of cancer.…”
Section: Expression Of Siahs In Primary Human Prostate Cancers and Pomentioning
confidence: 91%
“…Future experiments are anticipated on this interesting crosstalk. Immunohistochemistry of human prostate cancer specimens (n = 194) showed that mostly nuclear SIAH2 signals became decreased upon androgen deprivation therapy/prostatectomy (Table 1) and that SIAH2 levels increased upon disease recurrence [41]. These findings demonstrate that besides its regulation by female sex hormones (Table 1), SIAH2 is somehow controlled by male sex hormones.…”
Section: Regulation Of Siah Expression By Hormones and Cytokinesmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to SPOP, several other E3 ligases including Siah2 (Qi et al 2013), RNF6 (Xu et al 2009b), MDM2 (Lin et al 2002) and CHIP (Sarkar et al 2014) have been shown to mediate AR ubiquitylation, and these factors collectively enable another level of complexity in terms of AR regulation. Elucidating mechanisms underlying AR degradation has facilitated the rational design of proteolysis-targeting chimeras (PROTACs), which link an AR-binding element to a degron tag, such as an E3 ligaserecruiting moiety (Tang et al 2009) or a hydrophobic tag (Gustafson et al 2015), resulting in targeting of the AR to the UPS for degradation.…”
Section: :12mentioning
confidence: 99%
“…Conversely, knock-down of PMEPA1 leads to elevated levels of AR protein, and AR transcriptional targets like prostate-specific antigen (PSA) [21]. Among others, the E3 ubiquitin ligase Siah2 contributes to prostate cancer cell proliferation and also makes cells castration-resistant by selective regulation of AR transcriptional activity [23]. Usually, Siah2 targets transcriptionally inactive AR for degradation.…”
Section: Role Of the Ups Pathway In Prostate Cancermentioning
confidence: 99%